Text embedding using image steganography in spatial domain - Srilakshmi, P; Himabindu, Ch; Chaitanya, N; V. Muralidhar, S; V. Sumanth, M; Vinay, K (International Journal of Engineering and Technology, 2018)
This paper proposed novel approach of image steganography for text embedding in spatial domain. In the proposed embedding the message is dumped into the image with reference to a random generated key, based on this key the extraction of text is done from the image. So this method is a highly secured from eavesdropping and highly complex to identify the text data in the image and retrieving the text message from the message is also a resilient process. The extraction is only possible when the key is known.Â